The ancient pozzolanic mortars and concretes of Heliocaminus baths in Hadrian s Villa (Tivoli, Italy) - Columbu, Stefano (2016)
The aim of this work is the physical and mineralogical-petrographic characterization of the mortars from the Baths with Heliocaminus, a special and unique ar- chitectural building in the complex of the Hadrian’s Villa in Tivoli. Thirty samples were investigated for composition and physical properties (density, porosity, water absorption, me- chanical strength, particle size distribution of aggregate, etc.), representative of eight mortar groups: cubilia bedding mortar, brick bedding mortars, floor-coating and wall-coating bedding mortars, floor (rudus) and wall conglomerates (trullisatio), vault concretes, and lime plasters (arriccio). Physical param- eters, together with the microscopic analysis and binder/ aggregate ratio determined in three ways using image analysis (on thin sections and on specimens) and weight-data from dissolution of binder, have shown an interesting relationship between the physical-compositional characteristics and the function of mortars within the structure of the Heliocaminus baths. To identify the minerals and the reactant phases be- tween binder and aggregate, as well as the hydraulic degree, selected samples were analyzed with x-ray powder diffraction, thermogravimetry, and differential scanning calorimetry tech- niques. The obtained results provide a close relation between pozzolanic characteristics and physical-mechanical properties of the mortars (i.e., punching strength index).